Implementation of Traffic Monitoring Technology Using Smart Surveillance in Intelligent Transportation System - Rimra, Ihsan Lumasa; Lifwarda; Komanjali, Yuliano; Botto-Tobar, Miguel (SOTVI, 2023)
Currently transportation is very attached to human life, almost every family and even every adult human being has a vehicle as a means of transportation. Based on this, a conclusion can be drawn that population growth will trigger an increase in the number of vehicles in Indonesia. The implementation of Traffic Monitoring Using Smart Surveillance in the Intelligent Transportation System is research on information and communication technology in the transportation system in order to increase mobility, reduce congestion resulting from the buildup of vehicles in one lane, and be taken into consideration by road users before crossing a road section. This system uses the Background Subtraction method, and object detection. This system was created by utilizing OpenCV and Python programming language. This research obtained an accuracy of 93.1% on camera A and 93.5% on camera B in calculating passing vehicles in the test using simulations monitored via cameras in real time.